A Review of Important Activities and Studies 1968-69 - Planning Commission (Planning Commission, 1969)
As reported in the “A Review of Important Activities and Studies, 1967-68”, work on the formulation of the Fourth Five Year Plan was initiated after the National Development Council, at its meeting held on December 1 and 2, 1967, endorsed the view of the Planning Commission that the Fourth Five Year Plan might commence from 1969-70. In view of the change in the period to be covered by the Fourth Five Year Plan, as also in the light of the prevailing economic situation, a fresh exercise in aggregation giving the main framework of the Fourth Plan had become necessary, before the details of sectoral programmes and projects could be satisfactorily worked out.
Government of India Planning Commission